Etikonomi jurnal ekonomi Universitas Islam Negeri Syarif Hidayatullah Jakarta. (Fakultas Ekonomi & Ilmu Sosial, Universitas Islam Negeri Syarif Hidayatullah, 2002)
On socioeconomic, business development, Islamic banking, etc. studies in Indonesia.